Hip-hop et reggae : Unité dans l’usage des anglicismes et des jamaïcanismes, diversité de leur réalisation phonétique - Chodaková, Polina (Verbum – Analecta Neolatina, 2013)
This paper investigates the presence of loanwords in rap and reggae music, with a focus on their pronunciation. First, a corpus of 200 French and Czech songs is explored in search of numerous anglicisms, jamaicanisms and other lexical borrowings not listed in the dictionary Petit Robert 2012. We show that these neologisms are positioned in a center/periphery concentric scheme. Furthermore, by contrasting the phonemic inventories of the languages from a violable constraints perspective, the distribution of certain segments (affricates, glides, rhotic consonants) is shown in more detail. Interestingly, the loanwords do not seem to follow any diachronic pattern, and their distance from native vocabularies of French and Czech is not mirrored in the artists’ phonetic realisation. As a result, the great variation encountered is attributed to the musical stylisation, and the affiliation of the loanwords to the hip-hop and reggae sociolects.